Bidirectional wavelength-division multiplexing transmission over installed fibre using a simplified optical coherent access transceiver - M. S. Erkılınç (Nature Portfolio, 2017)
The signalling scheme used in access networks require electrical bandwidths many times greater than subscribers can utilise. Here, the authors describe a promising approach to achieve bidirectional transmission with bandwidth-efficient yet low-complexity coherent optical network unit transceiver.